Languages and indentieties in North Macedonia: Legal and political challenges to state formation - Marina Andeva; Ylber Sela; Lazo Matovski (University American College Skopje, 2022)
This paper examines the legal and political challenges to state formation in North Macedonia through analyzing the language use and linguistic rights of ethnic communities in North Macedonia. At first the paper gives a historical overview of the modalities of language rights protection in the country before and after its independence in 1991. The paper focuses on an analysis of the legal implications of the current regulations of the use of languages in the country and discusses how they affect the identities of ethnic communities as opposed to the formation of the multilingual and multiethnic state of North Macedonia. An examination of the forms and instruments of tackling linguistic rights in the country is carried out by discussing the requests, needs and rights of all constitutionally recognized ethnic communities. This paper will present the analytical content research conducted by the authors on the topic.
Keywords: 330; North Macedonia; language rights; power-sharing; policy; identity formation; multilingualism